2010
DOI: 10.1186/1471-2164-11-608
|View full text |Cite
|
Sign up to set email alerts
|

Consistent levels of A-to-I RNA editing across individuals in coding sequences and non-conserved Alu repeats

Abstract: BackgroundAdenosine to inosine (A-to-I) RNA-editing is an essential post-transcriptional mechanism that occurs in numerous sites in the human transcriptome, mainly within Alu repeats. It has been shown to have consistent levels of editing across individuals in a few targets in the human brain and altered in several human pathologies. However, the variability across human individuals of editing levels in other tissues has not been studied so far.ResultsHere, we analyzed 32 skin samples, looking at A-to-I editin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…As reflected by low variability in our data, we observed highly consistent levels of editing at all iGluR sites across individuals, which is in line with the results of recent studies that assessed editing in different molecules. 31,32 These results confirm that, as was reported for other targets, RNA editing of iGluRs is a tightly regulated process, emphasizing the importance of this posttranscriptional modification for the functionality of the glutamatergic system in the brain. 32 However, we did not detect any diagnosis-or suicide-specific alterations.…”
Section: Discussionsupporting
confidence: 76%
“…As reflected by low variability in our data, we observed highly consistent levels of editing at all iGluR sites across individuals, which is in line with the results of recent studies that assessed editing in different molecules. 31,32 These results confirm that, as was reported for other targets, RNA editing of iGluRs is a tightly regulated process, emphasizing the importance of this posttranscriptional modification for the functionality of the glutamatergic system in the brain. 32 However, we did not detect any diagnosis-or suicide-specific alterations.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies in humans have shown only limited effects of genetic variation on RNA editing. In one study, six A-to-I editing sites were found to be edited consistently across 32 individuals (Greenberger et al 2010). Another study found evidence of genetic variation for two (of 7389) A-to-I editing sites (Daneck et al 2012).…”
mentioning
confidence: 99%
“…For example, editing of specific adenosines within Alu repeats located in long double-stranded regions of human mRNAs occurs to a similar extent among different human individuals. 30 In addition, despite the presence of 2 homologous editing enzymes in mammals, certain adenosines in repetitive elements are specifically edited by only one of the ADAR enzymes. 31 Furthermore, editing site selection within noncoding regions appears to be regulated.…”
Section: Introductionmentioning
confidence: 99%